Establishing a new journal for systematic review products - Moher, David (BioMed Central, 2012)
Welcome to a new age in publishing systematic reviews. We hope the launch of Systematic Reviews will resonate with a broad spectrum of readers interested in using them in a variety of ways, such as providing comprehensive and up to date evidence for patient management, informing health policy, and developing rigorous practice guidelines. Systematic reviews are increasingly popular. Our journal is committed to publishing a wide variety of well conducted and transparently reported systematic reviews and associated research. We are open access and electronic and not confined by space and so offer scope for publishing reviews in detail and providing a modern and innovative approach to publishing. We look forward to participating in the voyage with all of our readers.